Impact of distilled water dealkalization on the geotechnical behavior of red mud - Ömür Çimen; Halil İbrahim Günaydın (PLoS ONE, 2025)
Red mud (RM), a highly alkaline residue from alumina production, poses environmental risks and limits its use in geotechnical applications due to its high soluble alkali content. This study investigates the effect of distilled water washing as a practical dealkalization method and assesses its impact on the geotechnical properties of RM. Both untreated and dealkalized samples were systematically characterized by chemical, mineralogical, microstructural, and geotechnical methods. The washing process reduced soluble alkali oxides while maintaining the primary crystalline phases, with only minor changes in diffraction peak intensities. SEM and BET analyses revealed particle agglomeration and alterations in mesoporosity, reflecting modifications in surface characteristics. These changes were consistent with a shift in particle size distribution and were accompanied by modifications in compaction characteristics, permeability, compressive strength, and swelling behavior, while plasticity indices showed only minor variations without altering the soil classification. The findings indicate that distilled water dealkalization is associated with measurable changes in the geotechnical response of RM by reducing soluble alkali ions while preserving the primary mineral phases and overall chemical composition. By relating the observed geotechnical changes to accompanying chemical and microstructural results, the study provides one of the few comprehensive evaluations of dealkalized RM, addressing an important gap in understanding its engineering potential.